2015
DOI: 10.1111/crj.12411
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of neuromuscular electrical stimulation in patients with COPD followed in intensive care unit

Abstract: This study indicates that pulmonary rehabilitation can prevent loss of muscle strength in ICU. Nevertheless, we consider that further studies with larger populations are needed to examine the impact of NMES and/or active and passive muscle training in bedridden ICU patients who are mechanically ventilated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 28 publications
4
60
3
4
Order By: Relevance
“…Assessment of the risk of bias based on the method formulated by the Cochrane Collaboration showed that relative to the selection bias aspect of "random sequence generation", two studies exhibited a low risk of bias ( 23 , 25 ) and the other two an uncertain risk of bias. ( 26 , 27 ) Relative to the selection bias aspect of "allocation concealment", all four articles exhibited an uncertain risk of bias. ( 23 , 25 - 27 ) In regard to performance bias - "blinding of participants and professionals" - three studies exhibited an uncertain risk of bias ( 23 , 25 , 27 ) and one study presented a low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of the risk of bias based on the method formulated by the Cochrane Collaboration showed that relative to the selection bias aspect of "random sequence generation", two studies exhibited a low risk of bias ( 23 , 25 ) and the other two an uncertain risk of bias. ( 26 , 27 ) Relative to the selection bias aspect of "allocation concealment", all four articles exhibited an uncertain risk of bias. ( 23 , 25 - 27 ) In regard to performance bias - "blinding of participants and professionals" - three studies exhibited an uncertain risk of bias ( 23 , 25 , 27 ) and one study presented a low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Of 25 full-text citations, nine studies with 276 participants fulfilled inclusive criteria to be reviewed. For papers excluded from this analysis, eight were due to study design,10,13,15,16,4043 four were due to the fact that stimulation was acupuncture,44–47 three11,24,28 had insufficient or inapplicable data, and one25 reported on the same group of participants as in another paper 26Figure 1 describes the different phase of the search process.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that muscle strength (quadriceps femoris and vastus glutei) was significantly improved and days to move from bed to chair decreased in the group treated with NMES, with no safety concerns. More recently, Akar et al 92 showed similar results on muscle strength and, in addition, they demonstrated a reduction of the levels of inflammatory cytokines [C-reactive protein, interleukin (IL)-6, and IL-8) in patients treated with NMES. In this case, the stimulator generated symmetrical biphasic square 50-Hz waves and the amplitude was switched between 20 and 25 mA with 6 seconds of contraction, 1.5 seconds of increase, and 0.75 second of decrease.…”
Section: Neuromuscular Electrical Stimulationmentioning
confidence: 77%